(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation. Coronary artery disease (CAD) continues to be the primary cause of mortality among elderly patients. In recent years, revascularization therapy centers have been established across nearly all regions of our country. Specifically, percutaneous coronary interventions (PCI) are employed to effectively treat patients with acute coronary syndrome (ACS) and post-infarction cardiosclerosis (PICS), aiming to enhance their quality of life. These endovascular procedures represent a highly effective therapeutic approach, significantly improving patients’ clinical status, enhancing physical exercise tolerance, and facilitating their return to routine daily activities.